2013
DOI: 10.3109/02699052.2012.750752
|View full text |Cite
|
Sign up to set email alerts
|

Olympic boxing is associated with elevated levels of the neuronal protein tau in plasma

Abstract: Olympic boxing is associated with elevation of tau in plasma. The repetitive minimal head injury in boxing may lead to axonal injuries that can be diagnosed with a blood test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
96
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 42 publications
5
96
1
Order By: Relevance
“…28,34 More recent publications using the more sensitive technology, Simoa, have demonstrated elevations of plasma tau after hypoxic-ischemic brain injury and sports concussion. 8,20 A recent study in boxers showed increased plasma tau immediately after a bout with head blows, but no loss of consciousness (LOC) followed by decrease in plasma tau to the prebout level after rest. 20 A most recent TBI study using Simoa showed increased plasma tau in service members who had sustained a TBI during military deployment compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28,34 More recent publications using the more sensitive technology, Simoa, have demonstrated elevations of plasma tau after hypoxic-ischemic brain injury and sports concussion. 8,20 A recent study in boxers showed increased plasma tau immediately after a bout with head blows, but no loss of consciousness (LOC) followed by decrease in plasma tau to the prebout level after rest. 20 A most recent TBI study using Simoa showed increased plasma tau in service members who had sustained a TBI during military deployment compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…8,20 A recent study in boxers showed increased plasma tau immediately after a bout with head blows, but no loss of consciousness (LOC) followed by decrease in plasma tau to the prebout level after rest. 20 A most recent TBI study using Simoa showed increased plasma tau in service members who had sustained a TBI during military deployment compared with controls. 28 In this study, total tau was significantly increased in the TBI group (mean level, 1.13 pg/mL), compared with the controls (0.63 pg/ mL), and increased levels were associated with increasing severity of the initial brain injury, increasing numbers of TBIs, and increasing severity of post-concussive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Shahim and colleagues identified elevations in serum T-tau both immediately and in the subacute period after SRC, with levels returning to baseline by return-to-play (22). Furthermore, Neselius et al found elevated blood T-tau levels in boxers at 1-6 days after a bout, compared to control subjects (46). Study design may partly account for the discrepancy between our findings and those of Shahim et al, as they compared T-tau levels in concussed athletes against pre-season baseline levels in males playing a single sport (ice hockey) (22), while we utilised in-season matched controls in males and females across several sports.…”
Section: Discussionmentioning
confidence: 99%
“…149 Tau levels in CSF and blood are elevated in boxers after a match, and CSF tau levels correlate with the quality and quantity of head impacts. 125,150 Recent evidence suggests that tau levels are elevated in the blood of ice hockey players after concussion, and may be useful in predicting recovery time. 126 Questions remain, however, with several studies reporting little or no value of serum cleaved tau for predicting post-concussion syndrome or long-term outcomes.…”
Section: Fluid-based Biomarkersmentioning
confidence: 99%